VIRTUAL PAKELIRAN WAYANG KULIT PURWA SURAKARTA STYLE DURING PANDEMIC COVID19: STUDY OF GARAP, FORM, FUNCTION, AND MEANING - Bambang Sunarto; Catur Nugroho; Sugeng Nugroho (Proceeding of International Conference on Art, Media, and Culture (ICAMAC), 2024)
Abstract                                                                                                This article discusses the virtual pakeliran of wayang kulit purwa during the Covid19 pandemic. The pandemic has forced puppeteers to continue to exist in the midst of society along with strict government restrictions. The presence of virtual pakeliran is an innovation created by the puppeteers as a solution to this problem. This article pays special attention to how a virtual pakeliran is created so that it is still accepted by the public. The material object chosen is the virtual pakeliran presented by Ki Purbo Asmoro and Ki Cahyo Kuntadi which is tracked through Youtube live streaming documentation. The concept used as a framework for analysis is the concept of Surakarta-style pakeliran garap, which consists of four elements of garap, namely the play, catur, sabet, and karawitan/ pakeliran accompaniment.  In addition, the post-structuralism approach is used as a perspective to see the form, function, and meaning of virtual pakeliran. The research method used is descriptive analytical through observation data on the documentation of virtual wayang performances. The virtual pakeliran during the Covid-19 pandemic shows the adjustment of the play to the phenomena that occurred, with a meaning that leads to hope and goodness. The form of virtual pakeliran tends to be packaged with a solid work presented through the use of streaming technology. This means that solid work affects various elements, including the work of the play, catur, sabet, and accompaniment. The collaboration process between conventional, concise, and compact arrangements results in an adaptive, responsive, and communicative virtual pakeliran. Virtual pakeliran functions as a creative space for puppeteers and entertainment media for the public during the pandemic. The important meaning in virtual pakeliran is in the form of hopes and prayers for a better life.